If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -10t = 3 Reorder the terms: -10t + 5x = 3 Solving -10t + 5x = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5x' to each side of the equation. -10t + 5x + -5x = 3 + -5x Combine like terms: 5x + -5x = 0 -10t + 0 = 3 + -5x -10t = 3 + -5x Divide each side by '-10'. t = -0.3 + 0.5x Simplifying t = -0.3 + 0.5x
| 8x^2+5=517 | | 3(x+4)+2(x+2)=41 | | 6b+18=7b+-21 | | 3b-24b= | | 5(5m-4)+11=66 | | (2w+2)(4w-1)=4w+1 | | 13=20+X | | x-3/8=15/8 | | 3x+20=9x-4 | | 7x+8=8(1-6x) | | 2y+3(y+2)= | | 4(x+5)=2(x+10) | | m/2=-41/2 | | -5y-9=1 | | (r-s)+(s-r)= | | 3y+2=4y+9 | | 3(3k+2)=6(4k-4) | | 5c*4e= | | 7x-60+3x+110= | | 3x+2x-6=3(2x-2) | | -a/6-7=-10 | | m-7.62=9.5 | | 4-3/8 | | 7.6a+10=78.4 | | 92=4(6m-1) | | 2y+2(y+2)= | | 7x+4=16+5x | | x/8=3;x | | -3.8=-4.1x+4.4 | | 2x+6-x=11 | | 4x-6=x+7+2x-15 | | M-23=47 |